Legal Framework duties of subjects subsoil (Journal of actual problems of jurisprudence, 2019)
The modern period of development of the Republic of Kazakhstan is characterized by increased state controland supervision in the field of environmental protection and natural resources, the creation of an optimalsystem of government, management of environmental and natural resource use with maximum efficiency.Keywords: environmental security, subjects subsoil, protection of the environment, the principles ofenvironmental protection, environmental management.